Monoamniotic Twin Pregnancy Discordant for Lethal Open Cranial Defect: Management Dilemmas - Sepulveda, W (2011)
Objective: To report the sonographic findings, prenatal courses, and management options in four cases of monoamniotic twin pregnancy complicated by a discordant, lethal open cranial vault defect. Methods: Cases were collected from two Latin American fetal medicine referral centers after the sonographic detection of a monoamniotic twin pregnancy in which one fetus was structurally normal and the other had a lethal open cranial vault defect. Three abnormal fetuses had acrania-anencephaly sequence and one had a large occipital encephalocele. The diagnosis was confirmed at referral, at which time umbilical cord entanglement was also diagnosed with color Doppler ultrasound in all cases. Results: Two cases were managed with selective termination, one of which required referral to a fetal surgery center abroad because this option was illegal in Chile. The other case underwent radiofrequency ablation of the fetal intra-abdominal umbilical vessels after the corresponding ethics and legal committees approved the procedure. In both cases, the non-anomalous twin was born after 35 weeks and had no perinatal complications. Expectant management was performed in the other two cases, resulting in the death of the normal twin at 25 weeks. Conclusions: Monoamniotic twin pregnancy discordant for severe cranial vault defect is a serious condition with a high risk of fetal demise of the structurally normal fetus. Our experience, although limited, suggests that aggressive management with selective termination of the abnormal twin and transection of its umbilical cord in these cases may prevent the demise of the structurally normal co-twin. © 2011 John Wiley & Sons, Ltd..